Global Competitiveness and Economic Growth: A One-Way or Two-Way Relationship? - Aleksandra Kordalska; Magdalena Olczyk (Institute of Economic Research (IER), 2015)
The Global Competitiveness Index is treated as a standard to measure the competitiveness of countries. Leaders look at it to make policy and resource allocation decisions because global competitiveness is expected to be related to economic growth. However, studies which analyze the empirical relationship between these two economic categories are very rare. It is still an open question in the literature whether economic growth can be used to predict future global competitiveness or the other way round. This paper empirically tests the relationship between the GCI and the economic growth rate by using a panel Granger causality analysis based on annual data for 114 countries divided into five groups by income criteria and covering the period 2006-2014. We confirm a strong unidirectional causality among the countries analyzed, i.e. GDP growth causes global competitiveness. Additionally, we find that the GCI is not successful in predicting economic growth for the majority of the 114 counties, with the exception of few large economies such as China, India, the United States and Russia.
Keywords: O40; O57; C23; F43; 330; Global Competitiveness Index; economic growth; panel Granger causality test